1991
DOI: 10.1093/tropej/37.3.100
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Epidemiological Study of Sickle Cell Anaemia in Saudi Arabia

Abstract: Ninety-nine Saudi Arabian children aged between 3 months and 15 years attending the sickle cell anaemia (SCA) clinic were studied using a review of case notes and an interview at clinic visits. All the patients come from the southwest and west area of Saudi Arabia. Despite the lack of infant screening for SCA, 73 per cent were diagnosed before the age of 3 years, reflecting severe early symptoms of the disease. The serious complications of SCA were two times higher, the number of admissions were three times hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is similar to the findings reported by Al Saqladi AW et al in Yemeni children and other parts of Saudi Arabia. 4,5 Retrospective data analysis with prospective cohort study done by Jain D et al in Maharashtra also reported the mean age of presentation at 3.85 years. 6 However in American and Jamaican cohorts the age of diagnosis is earlier and almost all children were diagnosed during infancy.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the findings reported by Al Saqladi AW et al in Yemeni children and other parts of Saudi Arabia. 4,5 Retrospective data analysis with prospective cohort study done by Jain D et al in Maharashtra also reported the mean age of presentation at 3.85 years. 6 However in American and Jamaican cohorts the age of diagnosis is earlier and almost all children were diagnosed during infancy.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might reflect a possible improvement in the management of SCD in Saudi Arabia; however, this point requires further evaluation [13–15]. The increased rates of stillbirth and IUGR reported among pregnant women with SCD could be owing to compromised placental blood flow secondary to maternal vaso‐occlusion of the placenta that leads to placental infarction and insufficient function [16]. The effect of chronic maternal anemia and pregnancy‐induced hypertension among patients with SCD further complicates this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed 2 different forms of SCD that are prevalent in Saudi Arabia [16,20]; the Asian β globin haplotype, which is more common in the Eastern region, and the Benin haplotype (African origin), which is more prevalent in the Western region. Clinically, the SCD encountered among patients from the Eastern region of the country has features consistent with elevated hemoglobin F levels and, more frequently, α‐thalassemia compared with patients from the Western region, where SCD appears to be more severe [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…Splenomegaly was common presentation in this study (45.7%) and this, in some patients, may progress to rapid blood sequestration in spleen causing acute splenic sequestration. Splenic sequestration crisis occurred in (6.6%) of our patients as compared to (7%) in Omanis (13) , (1%) in Eastern Saudi Arabia and (2.2%) in South Western Saudi Arabia (14,18) . All these rates are much lower than the reported rate of (25%) from Jamaica (15) as seen in table -4 .The incidence of aplastic crisis was (5.7%) in our cases which is more than that reported in Omanies (2%) (13) , and Eastern Saudi Arabia (2 %) (14) but markedly lower than the incidence reported from Jamaica (9%) (15) .…”
Section: Discussionmentioning
confidence: 57%